2020
DOI: 10.1364/oe.398619
|View full text |Cite
|
Sign up to set email alerts
|

Frequency comb enhanced Brillouin microscopy

Abstract: Brillouin light scattering (BLS) microscopy is a well established and powerful technique to study acoustic and magnetic excitations in the frequency domain with sub-micron spatial resolution. Many other spectroscopic techniques have benefited from the introduction of femtosecond laser sources to optically pump and stimulate the sample under investigation. In BLS microscopy, the use of femtosecond lasers as the excitation source introduces several challenges, primarily since the measured frequency shift is smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…tained SWs in a focused region close to the diffraction limit of the light, which is required to excite SWs with high wavevectors, where caustics can be formed. Here we overcome this limitation by utilizing a 1 GHz repetitionrate femtosecond laser comb capable of sustaining continuous SWs [24,26,27]. The emitted SWs contain a range of k-vectors and by slight detuning of the applied magnetic field off the ferromagnetic resonance (FMR), we observe X-shaped caustic SW patterns at around 70 • angles as predicted by theory.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…tained SWs in a focused region close to the diffraction limit of the light, which is required to excite SWs with high wavevectors, where caustics can be formed. Here we overcome this limitation by utilizing a 1 GHz repetitionrate femtosecond laser comb capable of sustaining continuous SWs [24,26,27]. The emitted SWs contain a range of k-vectors and by slight detuning of the applied magnetic field off the ferromagnetic resonance (FMR), we observe X-shaped caustic SW patterns at around 70 • angles as predicted by theory.…”
mentioning
confidence: 85%
“…A more in-depth description can be found in Ref. 27. Briefly, the pump-probe experiment uses a mode-locked femtosecond laser operating at 816 nm and a repetition rate of 1 GHz with 120 fs long pulses to induce rapid demagnetization.…”
mentioning
confidence: 99%
“…Recently, the BLS spectroscopy has been employed to produce FC-like signals originating from spin wave modes excited in a ferromagnetic thin film structure [ 18 , 97 ]. In those works, a thin Permalloy ( alloy) film—a standard building block of many magnonic and spintronic devices [ 82 ]—was deposited onto a sapphire substrate using a DC magnetron sputtering technique.…”
Section: Brillouin Light Scattering-based Frequency Combsmentioning
confidence: 99%
“…Note that studies reported in [ 18 , 97 ] did not aim to generate FC signals for use in applications where other kinds FCs have been typically used. Instead, a method of FC-enhanced BLS microscopy was introduced to coherently excite vibrational and spin wave modes in the sample.…”
Section: Brillouin Light Scattering-based Frequency Combsmentioning
confidence: 99%
“…Recently, the BLS spectroscopy has been employed to produce FC-like signals originating from spin wave modes excited in a ferromagnetic thin film structure [89,90]. In those works, a thin Permalloy (Ni 80 Fe 20 alloy) film-a standard building block of many magnonic and spintronic devices [73]-was deposited onto a sapphire substrate using a dc magnetron sputtering technique.…”
Section: Magnonic Bls-based Frequency Combsmentioning
confidence: 99%